The Effect of Health Education Using Booklet Media on Improving Knowledge and Attitudes Regarding Vulva Hygiene Among Adolescents - Selpi Tiara Putri; Sri Mulyati; Yuni Nurchasanah; Yulia Ulfah (Universitas Muhammadiyah Semarang, 2025)
Vulva hygiene is an effort to maintain the cleanliness of the external genital area of women. Lack of care can cause vaginal discharge, which is an abnormal discharge from the vagina that can smell and cause itching. In Indonesia, 90% of women have experienced vaginal discharge, and 60% of them occur in adolescent girls. This study aims to determine the effect of booklet media on the knowledge and attitudes of adolescent girls about vulva hygiene in preventing vaginal discharge. This study used a quantitative approach with a quasi-experimental design of the pretest-posttest type with a control group. The sample consisted of 80 adolescent girls selected through purposive sampling techniques. The data collection instrument was a questionnaire, and data analysis was carried out using the t-test. The results of the study showed that health education using booklet media about vulva hygiene significantly increased the knowledge and attitudes of adolescent girls, as evidenced by a p value <0.05 for both variables. Health education delivered through booklet media is more effective in increasing the knowledge and attitudes of adolescent girls compared to the use of Power Point media.